Informal Science Engagement via Extension Exhibits: A Pilot Evaluation of Adult State Fairgoers’ Experiences, Attitudes, and Learning at Raising Nebraska - Jamie Loizzo; Nathan W. Conner; Karen J Cannon Ph.D.; Elizabeth Janning; Jeffrey Rollins (Journal of Applied Communications, 2019)
Science communication and informal science education collide in the context of Extension state fair exhibits for engaging public audiences in critical agricultural and natural resource issues impacting people’s daily lives. A need exists to employ systematic communication and education theory and techniques to effectively deliver scientific information in informal learning spaces. In an effort to apply and expand systematic instructional design thinking and research in informal science learning, this study piloted a touchscreen iPad survey evaluation (n= 93; ages 19-66) of adult state fairgoers’ demographics, experiences, attitudes, and learning during their visit to a 25,000 square-foot facility featuring an Extension museum-quality exhibit at the Nebraska State Fair in 2016. The exhibit included content such as farmers’ and ranchers’ stories, food security, soil quality, and water flow via natural landscapes and irrigation. Survey results included fairgoers’ demographics and backgrounds, as well as insights into favorite exhibit features, attitudes toward agricultural and environmental issues, and exhibit experience and attitude differences between visitors with agricultural backgrounds versus non-agricultural backgrounds. Results showed respondents were predominantly Caucasian with ties to agriculture, preferred physical and electronic engagement pieces of the exhibit compared to static text panels, and expressed slight changes in attitudes about agriculture with larger shifts in attitudes about the role of science in agriculture. Recommendations include systematically developing Extension informal learning efforts and exhibits such as the one in this study by conducting needs assessments and evaluations, as well as expanding exhibit locations, access, and topics to reach more diverse demographics.
Keywords: Extension; exhibits; engagement; state fair; informal learning; science; attitude change